The Relationship Between Age Of The Mother With The Incidence Of Abortion And Types Of Delivery In Imelda Rsu Indonesia Workers In Medan - BR Sebayang, Wellina; T. Bolon, Christina Magdalena; Ritonga, Fitriana; Pasaribu, Dina (SEAN Institute, 2023)
Based on a preliminary study, the highest abortion rate was at the Uma Imelda Indonesian Migrant Hospital in Medan. The incidence of abortion at Imelda Medan General Hospital in 2020 was 8.14% of cases, in 2021 it increased to 7.95% of cases, and in 2022 it increased to 22.90% of cases. Teenage pregnancies at RSU Imelda Medan in 2020 amounted to 6.47% of cases, in 2021 it increased to 9.19% of cases, and in 2022 it increased to 25% of cases. Factors causing abortion include very young women aged <20 years and old women >35 years. Type of delivery also affects the incidence of abortion such as normal delivery for mothers < 20, 20-35, < 35 normal (31%, 56%, 48%) cesarean delivery (48%, 42%, 40% and curettage) 25%, 2% , 4%). General purpose Knowing the relationship between teenage pregnancy and the type of delivery and the incidence of abortion at the Indonesian Workers' Hospital Imelda Medan January -March 2022